Using Immediate Response Technology to Gather Electronic Health Data and Promote Telemental Health Among Youth. Issue 1 (31st July 2018) - Toscos, Tammy; Carpenter, Maria; Drouin, Michelle; Roebuck, Amelia; Howard, Abigail; Flanagan, Mindy; Kerrigan, Connie
Introduction: A sizeable number of youth are currently struggling with anxiety, depression, and suicidal thoughts, yet many will not receive treatment. We sought to better understand if immediate response technology (IRT) could be used to gather mental health care data and educate youth on telemental health (TMH) resources. Methods: Using an IRT imbedded within an interactive, media-rich school-based presentation, we gathered mental health history and preferences for TMH resources from 2, 789 adolescents with a wide range of demographic and psychological characteristics. Results: More than 80 percent of adolescents satisfied inclusion criteria for survey completion, and responses were statistically comparable across four diverse high school settings. Using Chi-squared analyses, we found that less than 10 percent of adolescents, especially girls and those with high depression/anxiety scores, had previously used TMH resources. After interacting with the IRT, many more (29 percent to 43 percent) expressed willingness to use these resources. Discussion: The IRT system was effective in gathering mental electronic health data, delivering targeted mental health education, and promoting positive attitudes towards TMH among adolescents. Conclusions: IRTs and other non-formalized technologies should be explored as cost-effective, easy-to-implement resources for electronic health data gathering and health care education.